2019
DOI: 10.1093/asj/sjz329
|View full text |Cite
|
Sign up to set email alerts
|

The Plastic Surgery Social Media Influencer: Ethical Considerations and a Literature Review

Abstract: Background Social media use has become a relevant tool in plastic surgery. These platforms are utilized for many reasons, such as business promotion. Although beneficial, social media can cause ethical dilemmas if used incorrectly. Objectives A review of the literature revealed what is understood about the implications of social media in regards to sponsorship/promotion. This paper aimed to create the foundation surrounding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 42 publications
0
33
0
4
Order By: Relevance
“…The topic of social media and influence in medicine has been discussed in other domains of healthcare. A review of the literature shows many fields, ranging from epilepsy, cardiovascular medicine, and plastic surgery as well as pathology [12][13][14][15], have investigated this area and come to varying [15]. The authors concluded that the while social media can be beneficial, the role of an influencer in medicine must be delicately balanced within the ethics of medicine, and this balance has not yet been fully addressed in terms of best practices [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The topic of social media and influence in medicine has been discussed in other domains of healthcare. A review of the literature shows many fields, ranging from epilepsy, cardiovascular medicine, and plastic surgery as well as pathology [12][13][14][15], have investigated this area and come to varying [15]. The authors concluded that the while social media can be beneficial, the role of an influencer in medicine must be delicately balanced within the ethics of medicine, and this balance has not yet been fully addressed in terms of best practices [15].…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature shows many fields, ranging from epilepsy, cardiovascular medicine, and plastic surgery as well as pathology [12][13][14][15], have investigated this area and come to varying [15]. The authors concluded that the while social media can be beneficial, the role of an influencer in medicine must be delicately balanced within the ethics of medicine, and this balance has not yet been fully addressed in terms of best practices [15]. An analysis of the use of social media platforms (Twitter, Facebook, Instagram, LinkedIn, and Doximity) and their associated use within academic Pathology programs showed high utilization with opportunities for networking and employment but had similar cautions of potential patient privacy issues.…”
Section: Discussionmentioning
confidence: 99%
“…Non-maleficence refers to a physician's obligation not to cause harm or adverse effects to a patient as a result of ineffective or absent care. Last but not least, justice entails distributing benefits, risks, and costs fairly, equitably, and appropriately, as well as treating patients with similar cases in the same way [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This confusion is amplified by social media accounts who falsely claim to be board-certified “cosmetic” or plastic surgeons, making it challenging for patients and the public to navigate social media pages and find qualified surgeons for the conditions and procedures they are seeking. Furthermore, it may be perceived that accounts with the greatest number of followers belong to more qualified or legitimate surgeons [ 11 ]. However, there is no evidence to support that the popularity of a social media account correlates with the highest level of care or surgical expertise.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no evidence to support that the popularity of a social media account correlates with the highest level of care or surgical expertise. There are many paths to gain popularity on social media including sponsorships, agreements with companies to promote certain products and services, and becoming a social media influencer [ 11 ]. Moreover, not all followers on social media accounts are real.…”
Section: Introductionmentioning
confidence: 99%